Quantitative Easing Program and Financial Market Volatility in Indonesia - Vahlevi, T. Muhd. Redha; Muharam, Harjum (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
This research aims to examine the impact of the USD money supply during and before quantitative easing program towards financial market volatility in Indonesia which is proxied by variance of financial market index such as IHSG, Gold Price in IDR, and Exchange Rate IDR/USD to find out the effect of the excess USD money supply on Indonesiaâs financial market volatility. This reseacrh has used monthly time series data of M1 of USD, IHSG, IDR/USD Exchange Rate, and Gold Price from December 2008 to December 2013. TGACRH in this research is used to find out wheter the volatility or variance at previous time affects volatility of these financial market index at present time and assymetric information is exist in the financial market index. The result showed that thereâs a difference between the effect of USD money supply to financial market index volatility in Indonesia during QE program and before QE program. Before and during QE program, USD money supply positively affects IDR/USD exchange rate volatiliy and IHSG volatility and negatively affects Gold Price volatility. During QE program, USD money supply negatively affects volatility of IDR/USD exchange rate and IHSG, and positively affects Gold Price volatility.